Transfer of English Teacher Training Skills: Teacher Trainers’ Observations - Kshetree, Arun Kumar; Bhusal, Tilak; Pokhrel, Prem Raj; Panthi, Badri Narayan (SNPRC Journal, 2025)
In order to prepare our country for the future, we need a good teacher education training program to help us grow. English language teaching (ELT) situation needs to be improved in Nepal and it is widely accepted that situation of ELT will be naïve unless we train the teachers in different ways. Most of the stakeholders believe that teacher training programs and the university curricula are more responsible for successful ELT classes. In such situation this paper intends to study and analyse the teacher trainers’ views and attitudes towards training programs for teachers. It is based on the interviews of the teacher trainers who have been training the English teachers of Lumbini province. It was basically about the performance of secondary level English teachers in the class and the transfer of training in the actual classes. After the analysis and interpretation of the ideas expressed by the trainers, their attitudes, suggestions as well as the problems of transfer of training skills have been presented in this paper. The results show that the situation of ELT is gradually developing because of training programs and they were found to be hopeful for bright future of ELT. Thus, the conclusions and results from this paper are supposed to be helpful for the teachers, trainers and the policy designers and ELT authorities to develop the ELT situation in Nepal.